Applying UTAUT To Understanding Factors Influence The Use Of Elearning Bpk Corporate University In Jfp Ap Training - Aditya Sujarminto; Annisa Putri (Journal of E-business and Management Science, 2023)
Decision making will always be based on valid and reliable data. The effectiveness and efficiency of information are a must for agencies to evaluate their programs. The process of conducting effective and efficient training for training participants to the training organizers. Innovation based on the use of the system has an important role in fulfilling learning services in the Badiklat PKN BPK RI environment. The implementation of training during the pandemic forced agencies to use a system that can run quickly and control the learning process. This study wants to evaluate the system used in the process of conducting training in the Badiklat PKN BPK RI using the UTAUT (Unified Theory of Acceptance and Use of Technology) method. The research sample comprises 55 Auditor Functional CPNS individuals from the Audit Board of the Republic of Indonesia in 2022. This research shows that social influence and behavioral intention have a significant and positive effect. However, Performance Expectancy (PE) and effort Expectancy (EE), do not affect Behavioral Intention. An optimal system is a system that can be used easily by users, if users cannot use the system, then there will be system failure because the data generated will be biased and invalid. Suppose the user has difficulty operating the system. In this case, it is better to immediately evaluate in the form of input and training to further improve the skills of users who use it.